Preparos e propriedades físicas de um solo arenoso para cana-de-acúcar e mandioca no Rio Grande do Sul - Fontanela, Eracilda (2012)
The growing demand for biofuels as alternative to petroleum-based fuels has instigated increased production of bioenergy crops. The southern half of Rio Grande do Sul, by having limited water resources for the production of soy, has received government incentives for the production of these crops, especially crops of sugar cane and cassava. However, there is need for more precise information regarding the proper management of these crops, and the influences of physical and hydraulic properties and mechanical soil on the growth and development of plants. Accordingly, this study aimed to determine the effect of different tillage systems on soil physical attributes, water and soil mechanics and its effects on the productivity of sugar cane and cassava. The study was conducted in the experimental area of the Soils Department, Federal University of Santa Maria in a Hapludalf. In two experiments were planted crops of sugar cane and cassava, in randomized blocks with three replications under different management systems and levels of compression: conventional tillage (CT) no tillage chiseled (NTC) no tillage (NT) and no tillage compacted (NTComp). Soil samples with preserved structure were collected for determination of physico-hydric soil density, pore size distribution curve of water retention, air and water flows, optimal water and compressive parameters: preconsolidation pressure (PP), compression index (CI) and elasticity of the soil. In addition, we calculated the indicators of soil quality: S ratio and relative density (RD) or degree of compression (GC). Soil preparation with mobilization (CT and NTC) alters the compacted soil, reducing soil bulk density and increased macroporosity and total porosity, but these effects are temporary and soil back to become thickened compromising the functionality of soil structure and plant development. A further compaction by traffic loader modifies the structure of Hapludalf, due to the increase in density and changes in distribution of soil pores, reducing macroporosity and total porosity, affecting the conductivity to water and air in the soil. The deeper layers were responsible for increased water storage in the soil. In the culture of cane sugar, NTC and NTComp retains higher water content, while the cassava crop, is the NT and NTC. Yield of both crops in association with the studied parameters, no-till soil management is offering the best physical condition and is indicated for production of sugar cane and cassava.